Facial skin follllicular hyperkeratosis of patients with basal cell carcinoma - M. V. Zhuchkov; Yu. S. Bychkova; M. A. Tarasova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
This article provides a clinical observation of paraneoplastic syndrome of a patient with basal cell carcinoma of skin. Authors present clinical features of the described for the first time, paraneoplastic retentional follicular hyperkeratosis of facial area.